Addressing forest policy and planning by combining participatory workshops and forest management decision support tools - Borges, J. G.; Marques, S.; Garcia-Gonzalo, J.; Rahman, A. U.; Bushenkov, V.; Sottomayor, M.; Carvalho, P. O.; Nordström, E.-M. (Natural Resources Institute Finland, Luke, 2016)
This STSM contributed to the ORCHESTRA objectives by outlining and evaluating a general approach for analysis of alternative forest policies by combining participatory workshops with advanced forest decision support tools. This approach was applied in workshops and the approach and results were evaluated by the participants.
Poster
Keywords: ecosystem services; collaborative planning; group decision making; multiple criteria decision methods; Pareto frontier